2020
DOI: 10.1096/fj.201903038r
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin ameliorates renal tubular injury in diabetic kidney disease via STAT3‐dependent mitochondrial homeostasis through SDF‐1α/CXCR4 pathway

Abstract: Mitochondrial abnormalities play critical roles in diabetic tubular injury progression. Dipeptidyl peptidase‐4 (DPP4) inhibitors are widely used antihyperglycemic agents that exert renal protective and positive effects against mitochondrial dysfunction in diabetic kidney disease (DKD). However, their underlying mechanism remains unclear. In this study, DPP4 upregulation, mitochondrial fragmentation, and altered mitochondrial dynamics‐associated protein expression were observed in the tubules of DBA2/J (D2) dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…IHC staining was scored independently by two pathologists [percentage of positive cells: five categories: 0 (<10%), 1 (10-25%), 2 (25-50%), 3 (50-75%), and 4 (75-100%); intensity: four categories (from low to high): 0, 1, 2, and 3; and a final IHC staining score (intensity score × percentage score)] was determined. 18…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…IHC staining was scored independently by two pathologists [percentage of positive cells: five categories: 0 (<10%), 1 (10-25%), 2 (25-50%), 3 (50-75%), and 4 (75-100%); intensity: four categories (from low to high): 0, 1, 2, and 3; and a final IHC staining score (intensity score × percentage score)] was determined. 18…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The membranes were blocked with 5% non-fat dry milk at 37°C for 1 h, and the proteins were probed against respective primary antibodies accordingly to previously published methods. 18 The β-actin was used as the internal control.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Zhang et al showed that a renal tubular injury in diabetic mice was suppressed by sitagliptin treatment. Moreover, sitagliptin restored mitochondrial fragmentation by regulating Drp1 expression and phosphorylation in the kidneys of diabetic mice and albumin-overloaded human kidney-2 (HK-2) cells [ 96 , 97 ]. In addition, the β 2 -adrenergic receptor (AR) agonist formoterol induced mitochondrial biogenesis and promoted recovery from AKI [ 98 ].…”
Section: Pharmacological Modulation Of Mitochondrial Dynamicsmentioning
confidence: 99%
“…Under diabetic conditions, excessive DPP4 would facilitate the transformation of its substrate SDF-1α into cleaved form, thus suppressing the SDF-1α/CXCR4/STAT3 pathway and impeding the translocation of STAT3 S727 into mitochondria. Diminished interaction of STAT3 and the mitochondrial fusion-associated protein OPA1 contributed to mitochondrial dysfunction in diabetic tubular cells, inducing DN progression [ 95 ].…”
Section: The Stat Signaling Pathways and Renal Diseasesmentioning
confidence: 99%